Optimization of the Air Compressor to Get Good Compressed Air In MV. Dewi Amabarwati - Diah Zakiah; Arif Hidayat; Benny Syahrir Abdurohman (Dinasti International Journal of Education Management And Social Science, 2022)
Transportation is one of the supporting factors for the smooth running of the economy in a country. One of the transportation is sea transportation because it is more effective and efficient. For this reason, the ship which is the main factor in the smooth operation of sea transportation must be prepared in its operation, the main thing that can support the smooth running of a ship is the smooth operation of the main engine. In general, the main engine on board the ship uses a diesel engine type, and the starting system uses compressed air where the compressed air is produced by the compressor auxiliary aircraft, so it can be said that the compressor has an important role in the operation of the ship. The compressor is one of the aircraft that is used to compress low-pressure air with higher pressure. During the operation of the main engine when the motion occurs, sometimes there are obstacles or obstacles that cause damage to the air compressor, so the compressor cannot work optimally. This results in the process of filling the main engine starting water for too long and can affect the smooth process of movement. The purpose of this study is to find out the obstacles or obstacles that can interfere with the main engine of the composer. The method used by the author in this study uses descriptive qualitative with several methods, namely, approach methods and data collection techniques. In the discussion in this study the author by finding several solutions to problems carrying out maintenance on engine room blowers and routines on the compressor as well as cleaning rust on the plunger and parts of the auto drain solenoid valve. The conclusions obtained in this study must maintain the air temperature in the engine room and always clean the high-pressure valve and low-pressure valve and pay attention to the compressor temperature so it doesn't get too hot because it can produce worse air.